(untitled) (REMUNOM, 2024)
Introduction: A simulator is a device or model used to train individuals, imitating situations they will encounter in real life. Surgical simulators, such as human cadavers, live animals, and virtual reality systems, recreate surgical situations for trainers to practice and hone their skills. Objective: To identify whether of applying simulation in surgery in undergraduate medicine and if they bring benefits to the student in the teaching-learning process. Methods: Data collection was performed with a survey of articles published in journals indexed in the Virtual Health Library (VHL), specifically using the MEDLINE and PUBMED databases. The descriptors used were: “High Fidelity Simulation Training”, “Simulation Training”, Surgery” and “Medicine”. In the selection of studies, inclusion criteria were considered: articles indexed in the aforementioned databases; Portuguese, English and Spanish languages; published between January 2018 and February 2022. Articles that did not meet the inclusion criteria were excluded from the analysis. Results: Simulation is a teaching method and has shown positive educational results, such as: better acquisition of knowledge, skills, behaviors and patient outcomes. The use of simulation in medical education is well established and enriches the curriculum. Patient simulators replicate patient care scenarios in a realistic environment working with a repeat methodology, this provides practice by minimizing the chances of medical error. Conclusion: The current evidence found during the research suggests that the skills acquired through training with simulators are positively transferred to the medical practice scenario, which corroborates with our objective of the research.